THE RELATIONSHIP BETWEEN DEPRESSION LEVELS AND QUALITY OF LIFE POST-FLOOD DISASTERS IN COMMUNITIES IN NANGGUNG DISTRICT BOGOR REGENCY - Aliyupiudin, Yufi; Yanti, Tisna; Lelono, Satrio Kusumo; Suryana, Akhmad Yani; Siswanti, Reny; Sulistyo, Fajar Adhie (Jurnal Keperawatan Respati Yogyakarta, 2022)
In 2013 – 2016 Indonesia experienced 7,835 floods. The incident caused 2,294 people died, 623 people were missing, 9,187 people were injured, 1,799,211 people were displaced, 8,460,772 people were disabled, 52,396 houses were heavily damaged, and 133,662 houses were slightly damaged. Indonesia, especially Java Island, experienced 509 floods which resulted in 201 deaths, 84 people missing, 322 injured, 92,678 people displaced, 971,602 people disabled, 4,515 houses heavily damaged, and 15,420 houses lightly damaged. West Java also experienced 56 floods in the same year. The flood caused 15 deaths, 2 injuries, 9,557 people displaced, 730,967 disabled people, 48 houses seriously damaged, and 154 houses lightly damaged. The sampling method in this research is accidental sampling technique with 60 respondents. The tools used in data collection were the WHO-Qol BREEF questionnaire to assess the quality and the Beck Depression Inventory (BDI) questionnaire to assess depression. The data analysis used was univariate and bivariate (Chi-square) analysis with SPSS program. The results of 60 respondents for the level of depression after the flood disaster in Nanggung Regency in 2021, 42 respondents (70%) experienced severe depression, 46 respondents (73.7%) had poor quality of life, There is a relationship between the level of depression and the quality of life of the community after the disaster flash floods in Nanggung Regency in 2021 with a p value of 0.034 (p value < 0.05). Keywords: Depression; Quality Of Life; Post-Flood Disasters